2020
DOI: 10.1101/2020.01.25.919399
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Divergent thermal challenges elicit convergent stress signatures in aposymbioticAstrangia poculata

Abstract: 7Corals are threatened worldwide due to rapidly warming oceans associated with anthropogenic 8 climate change. A growing body of work has explored how corals respond to heat stress, however, 9responses of corals across the full range of their thermal breadth are rarely explored even though 10 winter colds are also known to induce coral stress. Here, we leverage the temperate stony coral, 11Astrangia poculata, which naturally exhibits a facultative symbiosis with Symbiodiniaceae, to 12 explicitly examine how th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 86 publications
1
1
0
Order By: Relevance
“…When contrasting the heat stress response separately in symbiotic and aposymbiotic ramets of A. poculata, we found fewer differentially expressed genes between symbiotic control and symbiotic heat-stressed ramets (n=13) than we found between aposymbiotic control and heat-stressed ramets (n=76, Figure 5A). The overall low levels of differential expression align with recent work on aposymbiotic colonies of A. poculata, which demonstrated that seven times as many genes were differentially expressed under cold stress compared to heat stress in shortterm experiments (Wuitchik et al, 2020). In response to chronic heat stress, aposymbiotic colonies in the present study mounted a significant inflammatory response.…”
Section: Symbiotic Ramets Altered the Expression Of Fewer Genes Than supporting
confidence: 87%
“…When contrasting the heat stress response separately in symbiotic and aposymbiotic ramets of A. poculata, we found fewer differentially expressed genes between symbiotic control and symbiotic heat-stressed ramets (n=13) than we found between aposymbiotic control and heat-stressed ramets (n=76, Figure 5A). The overall low levels of differential expression align with recent work on aposymbiotic colonies of A. poculata, which demonstrated that seven times as many genes were differentially expressed under cold stress compared to heat stress in shortterm experiments (Wuitchik et al, 2020). In response to chronic heat stress, aposymbiotic colonies in the present study mounted a significant inflammatory response.…”
Section: Symbiotic Ramets Altered the Expression Of Fewer Genes Than supporting
confidence: 87%
“…Traits such as the potential to exist in multiple symbiotic states (symbiotically and aposymbiotically) living sympatrically (e.g. Astrangia poculata, aposymbiotic Astrangia do not harbor symbionts whereas their symbiotic counterparts harbor Breviolum psygmophilum, [38,39] will allow the study of facultative symbiosis ranging from cellular, to organismal, to ecological approaches [38,40,41]. Although scleractinian corals are considered non-model systems, they manifest PLOS ONE many qualities of model systems.…”
Section: Introductionmentioning
confidence: 99%